(untitled) (Fiep Bulletin - online, 2014)
It is understood that the education in the contemporary world is considered as a fundamental presupposition to reduce discriminations of some factors, among them the social. For that it was done necessary that the procedures adopted in the teaching through the sport, she had educational concerns in way to reach the child’s intellectual formation or of the adolescent. She meditates her that in physical education, especially in the school sport, it only is not enough to begin children in practice sporting, developing them in the motor aspect, but, to motivate them to participate indeed of the other disciplines existent in the school. Then, it was through the initiation to the basketball that grew the project entitled "Bola na Cesta ", that it is the initiation of the technical foundations of the basketball. It is understood that the practice of the sport activity, now, is of extreme importance for the health and the child’s development. Thinking about that, it was aimed at in this work to investigate the initiation to the Basketball contributes for the participant students’ of the research school income, in comparison with students of the same series that didn’t participate. The project grew in partnership among the (EEPGHM) State School of First Degree Profº Hugo Miele and UNESP - From São Paulo State University, through the Department of Physical education and financial aid of PROEX - Pró Rectory of Academical Extension. The research followed the descriptive design (THOMAS and NELSON, 2002). The sample was constituted by 19 school female in the age group among 12 to 14 years, enrolled among 5ªs to the 8ªs series of EEPHM in the city of Pres. Prudente, São Paulo State. The students’ final averages were consulted from 5ªs to the 8ªs series and she occurred comparison among the students that were submitted the initiation to the Basketball with the ones that didn’t participate in the same. After the comparison and analysis, it was ended that the activities of sporting initiation, besides beneficial to the health, also, she became effective in the school use.